HUMAN GRIT IN SHERMAN ALEXIE’S: The Absolutely True Diary of a Part-Time Indian - Krisdayanti Novita Manihuruk (Muse: Jurnal of Art, 2025)
This thesis explores the role of human grit: passion and perseverance in the development of the main character, Arnold Spirit Jr. in Sherman Alexie’s The Absolutely True Diary of a Part – Time Indian. Using mimetic theory and narrative qualitative methodology, this study examines how Junior’s determination to purse education and self-identity serves as resistance to the socio-economic limitations of reservation life. Despite poverty, racism, and personal loss, Junior exhibits high levels of grit, suggesting that passion and perseverance are essential for marginalized youth striving to achieve long – term goals. The findings confirm Duckworth’s view that grit is a more significant predicator of success than intelligence or talent.